The use of Aspergillus Niger for the removal of potassium and phosphorous from the iron ore of the Sishen iron ore mine, South Africa - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2009.